Hubungan indeks massa tubuh dengan profil lipid pada pasien diabetes melitus tipe 2 - Koampa, Pradika H.; Pandelaki, Karel; Wongkar, Marthen C.P. (Universitas Sam Ratulangi, 2016)
Abstract: Body Mass Index (BMI) is a measurement of nutritional status by calculating the ratio of height and weight. Type 2 Diabetes Mellitus (T2DM) is more common in a person with a BMI of more than normal. In patients with T2DM, there is lipid metabolism disorder, dyslipidaemia. Changes in lipid profiles consist of increased levels of total cholesterol, Low Density Lipoprotein (LDL), and triglycerides, and decreased levels of High Density Lipoprotein (HDL). This study aimed to obtain the correlation between body mass index and lipid profile in T2DM patients in Prof. Dr. R. D. Kandou Hospital Manado. This was a descriptive analytical study using patientsâ€™ medical record in Endocrine Clinic Prof. Dr. R. D. Kandou Hospital Manado from September to November 2015. The Pearson correlation test showed correlations between BMI and total cholesterol levels with r=0.037and p=0.763; between BMI and HDL levels with r=-0.249 and p=0.039; between BMI and LDL levels with r=0.091 and p=0,455; and between BMI and triglyceride levels with r=0.179 and p=0.142. Conclusion: Among T2DM patients, there were no significant correlations between body mass index and total cholesterol, LDL cholesterol, as wello as triglyceride levels. However, there was a significant correlation between body mass index and HDL levels. Keywords: body mass index, total cholesterol, HDL, LDL, triglycerides, T2DMÂ Abstrak: Indeks Massa Tubuh (IMT) merupakan salah satu pengukuran status gizi dengan menghitung perbandingan tinggi badan dan berat badan. Diabetes Melitus Tipe 2 (DMT2) lebih sering terjadi pada individu dengan IMT lebih dari normal. Pada pasien DMT2 terjadi gangguan metabolisme lipid yaitu dislipidemia. Perubahan profil lipid yang terjadi yaitu peningkatan kadar Kolesterol Total, Low Density Lipoprotein (LDL), dan trigliserida, serta penurunan kadar High Density Lipoprotein (HDL). Penelitian ini bertujuan untuk mengetahui hubungan antara IMT dengan profil lipid pada pasien DMT2di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ini deskriptif analitik dengan menggunakan data rekam medik pasien di Poliklinik Endokrin Bagian/SMF Ilmu Penyakit Dalam RSUP. Prof. Dr. R. D. Kandou Manado periode September â€“ November 2015. Hasil uji korelasi Pearson memperlihatkan nilai hubungan antara IMT dan kadar kolesterol total r = 0,037 dan p = 0,763 ; nilai hubungan antara IMT dan kadar HDL r = -0,249 dan p = 0,039 ; nilai hubungan antara IMT dan kadar LDL r = 0,091 dan p = 0,455; serta nilai hubungan antara IMT dan kadar trigliserida r = 0,179 dan p = 0,142. Simpulan: Pada pasien DMT2 tidak dijumpai hubungan bermakna antara IMT dengan kadar kolesterol total, kadar LDL, dan kadar trigliserida, namun terdapat hubungan bermakna antara IMT dengan kadar HDL.Kata kunci: IMT, kolesterol total, HDL, LDL, trigliserida, DMT2